'Enough is enough: this cycle of violence has to come to an end': Practical reasoning in the editorials during the extradition bill crisis of Hong Kong. Issue 4 (August 2021) - Pietra, John Della; Wang, Simon
Practical reasoning as an important form of argumentation in politics has received limited research attention in critical discourse studies despite the proposal of an analytical model. Focusing on argument development surrounding events related to the extradition bill crisis of Hong Kong, this paper analyzes 48 editorials published in the South China Morning Post during the crisis period adopting Fairclough's model. A number of recurrent themes have been identified in the corpus in association with the four argument components within the model – Claims, Goals, Values and Circumstances – which may increase understanding of the social contexts of the extradition bill crisis. It is further argued that, although Fairclough's model may not capture the arguments in individual editorials comprehensively, the model can be usefully applied to analyze a collection of interrelated editorials to reveal more insights about an ongoing political crisis.